Solving the multi-period water distribution network design problem with a hybrid simulated anealling - Bermudez, Carlos Alberto (2019)
This work presents an optimization technique based on Simulated Annealing (SA) to solve the Water Distribution Network Design problem, considering multi-period restrictions with time varying demand patterns. The design optimization of this kind of networks is an important issue in modern cities, since a safe, adequate, and accessible supply of potable water is one of the basic necessities of any human being. Given the complexity of this problem, the SA is improved with a local search procedure, yielding a hybrid SA, in order to obtain good quality networks designs. Additionally, four variants of this algorithm based on different cooling schemes are introduced and analyzed. A broad experimentation using different benchmark networks is carried out to test our proposals. Moreover, a comparison with an approach from the literature reveals the goodness to solve this network design problem.